Factors affecting purchase intention in E-commerce platform in VietNam. Examples of Shopee, Lazada, Tiki - Nguyen, Thuy Duong (H. : ĐHQGHN, 2020)
The purpose of the paper is to review the literature on theories affecting consumers' online purchase intention and the indicators influencing customers' purchase intention at three e-commerce companies in Vietnam: Shopee, Lazada and Tiki.